2021
DOI: 10.3390/ijerph182111183
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stressors Suffered by Women with Gynecological Cancers in the Aftermath of Hurricanes Irma and María in Puerto Rico

Abstract: Background: Hurricanes are the immediate ways that people experience climate impacts in the Caribbean. These events affect socio-ecological systems and lead to major disruptions in the healthcare system, having effects on health outcomes. In September 2017, Puerto Rico (PR) and the United States Virgin Islands (USVI) experienced one of the most catastrophic hurricane seasons in recent history (Hurricane Irma was a Category 5 and Hurricane María was a Category 4 when they hit PR). Objective: This study examines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“… 30 Equally important, a prior study from our team also identified that, following Hurricane Maria, environmental stressors such as lack of potable water, heat and uncomfortable temperatures, poor air quality, noise pollution from generators, and pests (eg, mosquitos, rats) were top concerns in PR. 24 Future disaster plans should include strategies to mitigate these environmental stressors as they threaten public health and the well-being of populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 Equally important, a prior study from our team also identified that, following Hurricane Maria, environmental stressors such as lack of potable water, heat and uncomfortable temperatures, poor air quality, noise pollution from generators, and pests (eg, mosquitos, rats) were top concerns in PR. 24 Future disaster plans should include strategies to mitigate these environmental stressors as they threaten public health and the well-being of populations.…”
Section: Discussionmentioning
confidence: 99%
“…Additional details about our methodology are available elsewhere, including a report on environmental stressors experienced by gynecologic cancer patients and oncology care providers and administrators. 24 The Institutional Review Board of the University of Puerto Rico Medical Sciences Campus approved the study protocol (#A1810418 approved on August 30, 2018), including the qualitative work involving both gynecologic cancer patients and oncology care providers and administrators.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter study, mortality began to increase at HI thresholds around 31°C, around the values we present in Table 1. Second, uncomfortable temperatures in the aftermath of Hurricane María were among the top concerns of cancer patients and health‐care providers and administrators (Méndez‐Lázaro et al., 2021). Finally, Bobb et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study, mortality began to increase at HI thresholds around 31°C, around the values we present in Table 1. Second, uncomfortable temperatures in the aftermath of Hurricane María were among the top concerns of cancer patients and health-care providers and administrators (Méndez-Lázaro et al, 2021). Finally, Bobb et al (2014) showed that larger increases in central air conditioning prevalence tended to have slightly larger reductions in heat-related mortality risk over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation